(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The aim of this article is to justify the potential of technologies for processing secondary raw materials and to investigate the effectiveness of developing professional competences in future teachers of labor education and technology through the utilization of upcycling technology in the design of eco-bags. Project activity focuses on fostering critical thinking and portrays the pedagogical process as a system based on the theory of universal human values, humanization, a person-oriented approach, and the priority of subject-subject relations. It proves to be effective in shaping the personality of future teachers. The main features of the process of designing eco-bags using upcycling technology are determined to be interdisciplinary, communicative, and dynamic, facilitated by the use of information services of social networks. The process emphasizes environmental friendliness under the conditions of recycling secondary raw materials and involves creative project and practical activities. Pedagogical conditions for project activity in eco-bag upcycling are defined through provisions such as structuring the project and its stages, setting educational goals and tasks, implementing an integrated program of technological activity, developing a criterion basis for determining the levels of educational achievements, and creating information-subject and material-technical support for the educational process. Collaboration among teachers of general and professional training cycles is highlighted for content coordination, organization of training, and improvement of educational, methodological, and software training for processing secondary raw materials. The work employs methods of theoretical and empirical research, including analysis and synthesis to clarify main concepts and categories of learning technologies for processing secondary raw materials for future teachers of labor education and technology. It also involves the study of psychological-pedagogical and scientific-methodical literature and advanced pedagogical experiences related to learning technologies in higher education institutions, enabling the identification of regularities and formulation of conclusions on the investigated problem.